The Site of Calcium Binding in Relation to the Activation of Myofibrillar Contraction - Fuchs, Franklin (The Rockefeller University Press, 1968)
Skeletal muscle myofibrils, in the presence of 2 mM MgCl(2) at pH 7.0, were found to have two classes of calcium-binding sites with apparent affinity constants of 2.1 x 10(6) M (-1) (class 1) and ∼3 x 10(4) M (-1) (class 2), respectively. At free calcium concentrations essential for the activation of myofibrillar contraction (∼10(-6) M) there would be significant calcium binding only to the class 1 sites. These sites could bind about 1.3 µmoles of calcium per g protein. Extraction of myosin from the myofibrils did not alter their calcium-binding parameters. Myosin A, under identical experimental conditions, had little affinity for calcium. The class 1 sites are, therefore, presumed to be located in the I filaments. The class 1 sites could only be detected in F actin and myosin B preparations which were contaminated with the tropomyosin-troponin complex. Tropomyosin bound very little calcium. Troponin, which in conjunction with tropomyosin confers calcium sensitivity on actomyosin systems, could bind 22 µmoles of calcium per g protein with an apparent affinity constant of 2.4 x 10(6) M (-1). In view of the identical affinity constants of the myofibrils and troponin and the much greater number of calcium-binding sites on troponin it is suggested that calcium activates myofibrillar contraction by binding to the troponin molecule.